Novel Compounds Synergize With Venetoclax to Target KMT2A-Rearranged Pediatric Acute Myeloid Leukemia - Tregnago, Claudia; Benetton, Maddalena; Da Ros, Ambra; Borella, Giulia; Longo, Giorgia; Polato, Katia; Francescato, Samuela; Biffi, Alessandra; Pigazzi, Martina (Frontiers in Pharmacology, 2022)
In pediatric acute myeloid leukemia (AML), fusions involving lysine methyltransferase 2A (KMT2A) are considered hallmarks of aggressive AML, for whom the development of targeted specific therapeutic agents to ameliorate classic chemotherapy and obtain a complete eradication of disease is urgent. In this study we investigated antiapoptotic proteins in a cohort of 66 pediatric AML patients, finding that 75% of the KMT2A-r are distributed in Q3+Q4 quartiles of BCL-2 expression, and KMT2A-r have statistically significant high levels of BCL-2, phospho-BCL-2 S70 and MCL-1, indicating a high anti-apoptotic pathway activation. In attempt to target it, we tested novel drug combinations of venetoclax, a B-cell lymphoma-2 (BCL-2) inhibitor, in KMT2A-MLLT3, for being the most recurrent, and KMT2A-AFDN, for mediating the worst prognosis, rearranged AML cell lines. Our screening revealed that both Bromodomain and Extra-Terminal Domain (BET) inhibitor, I-BET151, and kinase inhibitor, sunitinib, decreased BCL-2 family protein expression and significantly synergized with venetoclax enhancing KMT2A-r AML cell lines death. Blasts t(6;11) KMT2A-AFDN rearranged, both from cell lines and primary samples, were shown to be significantly highly responsive to the combination of venetoclax and thioridazine, with synergy being induced by a dramatic increase of mitochondrial depolarization that triggered blasts apoptosis. Finally, efficacy of novel combined drug treatments was confirmed in KMT2A-r AML cell lines or ex vivo primary KMT2A-r AML samples cultured in a three-dimensional system which mimics the bone marrow niche. Overall, this study identified that by an high throughput screening the most KMT2A selective drugs converged in different but all mitochondrial apoptotic networks activation, supporting the use of venetoclax in this AML setting. Novel drugs combinations here unveiled provide a rationale for evaluating these combinations in preclinical studies to accelerate the introduction of targeted therapies for the life-threatening KMT2A-AML subgroup of pediatric AML.